DINAMIKA TATA KELOLA PERUSAHAAN: HUBUNGAN ANTARA DEWAN DIREKSI DAN STRATEGI ORGANISASI - Jayadi, Usman; Mustofa, Amirul; Yunus, Eddy (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This article explores the relationship between corporate governance and sustainability strategies in a global context. The study highlights the crucial role of boards of directors in formulating and overseeing company strategies, especially when facing challenges related to social and environmental sustainability. Boards are responsible for ensuring that companies focus not only on short-term financial gains but also on sustainable strategies that consider social and environmental impacts. Board diversity, including experience, skills, and backgrounds, plays an essential role in making more innovative and adaptive strategic decisions in response to market changes and global policies. Furthermore, good corporate governance strengthens corporate social responsibility (CSR) and positively impacts the long-term performance of companies. This study provides insights into the challenges boards face in managing risks and aligning long-term business goals with the expectations of other stakeholders.